Analyzing the Work-Life Balance with Religiosity on Career Women - Lathiefa Rusli; Aqidah Halimatus Saadah; Yayan Firmansah; Ahmad Setiyono (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2024)
The study aims to analyze the work balance on career women with religiosity as the supporting factor. The rapid change on values in society regarding to career women has been increased. It causes the development of career women to face some dual roles, for example to be a career woman, a mother, or a wife. This condition results in demands for career women to give full attention to work as well as the household matters. Work-Life balance (WLB) is needed to balancing the priority of time and place between in working place and non-working place. The research conducts a qualitative method in case study with purposive sampling. The subjects of the research were women ages around 28-year-old to 35-year-old, housewife, mother of one children or more, and at one time working as faculty members teaching in colleges and universities. In result, the subject has been able to balance the Personal Life Interference with Work (PLIW) and Work Interference with Personal Life (WIPL) in low influence on the Work Life Balance (WLB). While the Personal Life Enhancement of Work (PLEW) has medium influence on the Work Life Balance (WLB), and Work Enhancement of Personal Life (WEPL) has slightly influence on Work Life Balance (WLB).